Low voltage operation electrostatic comb drive micro-mirror for laser scanning display - Chu, Hoang Manh; Ngoc, Hung Vu; Hane, Kazuhiro (Vietnam Journal of Mechanics, 2012)
Electrostatic comb drive micro-mirror has limitation of high operation voltage, which has limited its practice use. Recent developments in decreasing operation voltage are promising for mobile micro-mirror. Especially, the operation voltage is decreased substantially by removing the air friction of comb-drive micro-mirror at a high resonant frequency when the mirror is operated at low pressure. Removing simultaneously the air friction and anchor loss, electrostatic comb-drive micro-mirror operating at a few voltages at a high resonant frequency becomes possible. This paper presents our recent developments as well as emerging techniques introduced in literature for decreasing the operation voltage of electrostatic comb drive micro-mirror. Methods for decreasing the operation voltage at large rotation angle and high scan frequency for application in the laser scanning display are focused to discuss in this paper.